2018
DOI: 10.1101/452060
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparison of antigen-specific T cell responses induced by six novel tuberculosis vaccine candidates

Abstract: Eradication of tuberculosis (TB), the world's leading cause of death due to infectious disease, requires a highly efficacious TB vaccine. Many TB vaccine candidates are in preclinical and clinical development but only a few can be advanced to large-scale efficacy trials due to limited global resources. We aimed to perform a statistically rigorous comparison of the antigen-specific T cell responses induced by six novel TB vaccine candidates and the only licensed TB vaccine, Bacillus Calmette-Guérin (BCG). We pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…However, despite the promising results of the M72/AS01E vaccine with 49.7% VE in QFT+ individuals (14), more efficacious vaccines are likely needed to end the epidemic (15). As the first generation of TB vaccine candidates has moved into more advanced clinical trials, there is a recognized need to diversify the vaccine pipeline to maximize the chance of bringing improved TB vaccines into widespread use (18,45,46). Such diversity can come in the form of antigenic composition, delivery vector and immune response functionalities.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the promising results of the M72/AS01E vaccine with 49.7% VE in QFT+ individuals (14), more efficacious vaccines are likely needed to end the epidemic (15). As the first generation of TB vaccine candidates has moved into more advanced clinical trials, there is a recognized need to diversify the vaccine pipeline to maximize the chance of bringing improved TB vaccines into widespread use (18,45,46). Such diversity can come in the form of antigenic composition, delivery vector and immune response functionalities.…”
Section: Discussionmentioning
confidence: 99%
“…Different methods have been implemented to develop more effective novel TB vaccines, and among these methods, subunit vaccines have shown great promise 19 i.e., the variety of epitopes in the Mtb protein antigens constituting the subunit vaccine. Besides computational studies, some studies had endeavored to evaluate the human T cell immune responses to multiple Mtb subunit vaccines empirically 20,21 and using data from clinical trials, respectively [22][23][24] . Rodo et al recommended that the identification of vaccines with distinctive immune response features may increase the probabilities of finding a safe vaccine 21 and provided valuable information on the potential production of the Mtb vaccine.…”
mentioning
confidence: 99%
“…The greatest potential for immune insight would be if the leading candidate TB vaccines induced a diverse immune response. However, in a recent comparison of antigen-specific T cell responses from human clinical trials, the functional profiles suggested a lack of response diversity, with the main difference in the magnitude of response [211]. This comparison involved AERAS-402, H1:IC31, M72/ASO1E, ID93+ GLA-SE, H56:IC31 and MVA85A [211].…”
Section: Correlates Of Protectionmentioning
confidence: 99%